Switched-Capacitor Filter Optimization with Respect to Switch On-State Resistance and Features of Real Operational Amplifiers - J. Hospodka; L. Dolivka (Radioengineering, 2007)
The optimization of a switched-capacitor filter, which implements a biquadratic section, is described in this paper. The aim of the optimization is to obtain a required magnitude frequency response of the filter. The optimization takes into account both one of the features of real switches - their on-state resistance, and the features of real operational amplifiers - finite voltage gain and finite unity-gain bandwidth. An optimal dynamic range is to be achieved as well. The differential evolution - a kind of evolutionary algorithms - is employed for the optimization. The filter is designed by the usual way with ideal switches and ideal operational amplifiers at first. The analysis of this filter with real switches and real operational amplifiers proves that there is a significant difference between its magnitude frequency response and the one with ideal components. Hence, the optimization is applied for finding component values so that the magnitude frequency response is as similar to the one with ideal components as possible. As for other main real features of operational amplifiers - input and output resistance - it is shown that their effect is small.